Analysis of the Financial Performance of the Regional Government of West Lombok Regency - Ni Nengah Adenita Mahitna; Abdul Manan; Eka Agustiani (Tinta Emas Institute, 2023)
This study analyzes the Financial Ratio of the West Lombok Regency Government's Regional Budget Revenue and Expenditure (APBD) from 2018 to 2022. Using a descriptive method, it aims to depict how financial ratios assess the government's financial performance. Results indicate that the regional independence ratio follows an instructive pattern. The effectiveness ratio is deemed ineffective, while the Efficiency Ratio over the last five years is efficient. The operating expenditure activity ratio meets good criteria. Assessing growth ratios, revenue and expenditure in West Lombok Regency have positively increased. Future recommendations include the government intensifying and extending current revenue sources to enhance independence. To boost effectiveness, realistic targets should be set based on the region's potential, preventing overestimation. The West Lombok Regency Government should optimize past growth and expenditure as a reference for future planning while striving to maintain and increase revenue and expenditure realizations annually.